PEMANFAATAN EKSTRAK UBI JALAR UNGU (Ipomea batatas L.) SEBAGAI SUMBER PREBIOTIK PAKAN KOMERSIL PADA BUDIDAYA IKAN MAS (Cyprinus carpio) - M. Mutawalli Wira Supati; Salnida Yuniarti Lumbessy; Dewi Putri Lestari (Journal of Fish Nutrition, 2021)
Goldfish is one of the freshwater cultured fish that is favored by the community both for consumption and as ornamental fish. Sweet potato (Ipomea batatas L.) is a plant that can be used as a prebiotic in fish feed. Sweet potato (I. batatas L.) is an annual plant that grows in the tropics. Sweet potatoes contain lots of carbohydrates, provitamin A, B vitamins, vitamin C, minerals, and a little fat and protein. This research is an experimental study using Completely Randomized Design (CRD) with 4 treatments and 3 replications each, so the number of experimental units is 12 units. P1 : commercial feed (control), P2: purple sweet potato extract 4 ml / 100 g feed, P3: purple sweet potato extract 8 ml / 100 g feed, P4: purple sweet potato extract 12 ml / 100 g feed. The data obtained were tested using Analysis of Variance (ANOVA) at a 95% confidence level through the SPSS program to determine the effect of each treatment. Keywords: Purple Sweet Potato Extract, Carp, Growth, Prebiotics, Nutrient Retention.